PRESIDEN SBY DAN POLITIK PENCITRAAN : Analisis Teks Pidato Presiden SBY dengan Pendekatan Retorika Aristoteles - S. Luhukay, Marsefio (Institute of Research and Community Outreach - Petra Christian University, 2007)
Systematically rhetoric knowledge was firstly developed in Greece. The first systematic elucidation on speech cleverness in Greek is well known as Techne Rhetorike, it means knowledge on speaking arts. In world history, speech cleverness was a primary instrument to influence masses. Language was used to convince others. Such capability is generally owned by prominent figures or statesmen such as presidents. In view of rhetoric importance as part of knowledge that include in discipline of communication knowledge, so the researcher was interested in observing and analyzing speeches by the incumbent president, Susilo Bambang Yudhoyono (SBY), that was well known as imaging politics, he has frequently displayed it while speaking before publics through addresses or other agendas in front of mass media or publics. Findings on examination of President SBY' Speech Texts that the most influential one for audiences was ETHOS. The ethos side was really reflected from the introductory section aimed at substantiating communicator's credibility. There were three aspects in Ethos namely Intelligence, Character, and Goodwill. The three aspects were contained in speeches of President SBY and the most dominant and strong one was Character aspect. It was reflected by sentences in his speeches that strove to portray himself as a personage, who is honest and trustworthy, that has empathy to societies.